Root Anatomy: Preparing, Imaging, and Analyzing Maize Root Cross-Sections - Sidhu, Jagdeep Singh; Schneider, Hannah M (Cold Spring Harbor protocols, 2024)
Root anatomy plays a critical structural and functional role in the maize root system, and regulates edaphic stress tolerance. The function and genetic basis of several maize root anatomical traits for stress tolerance have been demonstrated. Leveraging root anatomical traits in maize thus holds great potential for developing cultivars with greater nutrient and water efficiency. Key for such approaches is the ability to characterize the root anatomy of plants of interest. Here, we outline a systematic method for preparing, imaging, and analyzing maize root cross-sections. The protocol describes root sectioning (by hand or using a vibratome), preparation of microscope slides and toluidine blue staining, imaging under a light microscope, and both manual and semiautomated methods for anatomical feature extraction from images. The protocol enables the visualization and quantification of various anatomical tissues and traits, and its simplicity, adaptability, and accessibility make it an ideal choice for both small- and large-scale phenotyping studies in maize and other plant species. This standardized protocol provides researchers with a comprehensive methodology to accurately dissect root structures, enabling in-depth analyses that are essential for understanding plant growth, development, and adaptive value for stress tolerance.